EVALUATING THE TAX PAYING OF INCOME TAX AND LOCAL TAX ON CATERING SERVICE COMPANY (CASE STUDY IN CV. ABC IN PASURUAN) - Yulfemri, Neysa Rakmasari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
Taxpayers frequently do mistakes while implementing the taxes. Taxpayers tends to do errors caused by lack of education. CV ABC is the family business providing catering services in one of the cities in East Java. In running its business, CV. ABC fulfils its tax obligations by paying income tax in accordance with Government Regulation number 46 of 2013. This study aims to evaluating the tax paying of income tax conducted by CV. ABC in 2015. This research is qualitative with case study approach using interviews and documentation to collect the data. The result shows that the main problem experienced by the company is a wrong implementation type of taxes. Due to sales in 2014 is more than 4.8 billion Rupiah. The Implementation of tax in 2015 should be based on tariff as stipulated on regulation number 36 year 2008 concerning Income Tax instead of based on Government Regulation number 46 year 2013 about income tax from business with a certainty sales. Since CV. ABC cooperated with PT. X, other types of taxes are conducted based on income tax article 23 and restaurant tax. Those errors and unpaid taxes lead CV. ABC to be set at administration sanctions and it is going to be worse if CV. ABC do not report the errors immediatelyKeywords: Tax Paying, Income Tax, Local Tax